2022
DOI: 10.1002/vms3.753
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sub‐acute co‐exposure to WIFI (2.45 GHz) and Pistacia lentiscus oil treatment on wound healing by primary intention in male rabbits

Abstract: Background The bioeffects of WIFI on cutaneous wound healing remains unexplored. In addition, several medicinal plant products including lentisk oil have been shown to interfere with wound healing process. Since the use of this oil is increasing, the co‐exposure (WIFI‐Lentisk oil) assessment is of paramount importance. Objectives We aimed in the present study to investigate the effects of WIFI exposure as well as the application of Pistacia lentiscus oil on sutured wounds (SW). Methods New Zealand male rabbits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Therefore, researchers suggested that P. lentiscus oil and WIFI signals should not be used together to treat wounds. Linoleic acid and α-tocopherol were suggested as the main responsible components for wound healing activity (38).…”
Section: Pistacia Lentiscusmentioning
confidence: 99%
“…Therefore, researchers suggested that P. lentiscus oil and WIFI signals should not be used together to treat wounds. Linoleic acid and α-tocopherol were suggested as the main responsible components for wound healing activity (38).…”
Section: Pistacia Lentiscusmentioning
confidence: 99%